The Durability of materials and its effect on Architectural Monumentality (Arabic Paper) - Hussein, Maryam Safaa (Al-Nahrain Journal for Engineering Sciences, 2017)
From centuries , the human struggle against the forces that effected on its shelter and try to conserve it , to obtain stable structure that protect him from the external forces and meets him desire to conserve this structure as cultural inheritance from the past ._x000D_ The development in architect possibilities push him to search about building not just as a distinctive design among the public pattern of building , and meet it desire of eternity and crossing the time barrier towards the durability ._x000D_ As the visual part that we can realized physically need for materials having the advantages of the durability, the research supposed "The relation of the monumentality of architecture in its physical part with the main three substrates of the durability of building materials that presented in : climate , time and human " the research focus on this substrates and its effect to arrive to monument buildings ._x000D_ The research try to define the vocabularies of durability and monumentality and abstracting three substrates that forming its assumption and the research indicates mainly to the importance of the architect knowledge of the durability of materials after choosing and using in building and know every substrate from the main three supposed substrates that effected on it during the life service that supposed to be work in it, and define nanotechnology in building materials and its effect on durability._x000D_ Finally the research take a research samples that tested in the research assumption for the three substrates that effected on the durability of material and its mirror on the monumentality arriving to the final results and recommendation.